PELATIHAN GOAL SETTING “GOAL GETTER” UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - baroroh, Ema Zati; amalia, Kiki; Asri Azzahra, Mia; Putri, Santi Ramadhani (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Low learning motivation is a common challenge for students, especially those with busy schedules at school and in Islamic boarding schools (pesantren). This study aims to test the effectiveness of the "Goal Getter" goal-setting training in enhancing students' learning motivation in pesantren. Using a one-group pre-test post-test pre-experimental design, the study involved seven eighth-grade students at SMPI X. Learning motivation was measured using a Learning Motivation Scale, covering indicators of drive, commitment, initiative, and optimism. The Wilcoxon Signed-Rank test showed a significant increase in learning motivation after the intervention (Z = .043, p < .05). Qualitative findings from observations and worksheets revealed increased enthusiasm, self-confidence, and active participation from the students. The training consisted of two sessions, including motivational material, dream tree visualization, goal setting using the SMART method, and reflective discussions. The interactive approach helped students set more focused and meaningful goals. The results of this study demonstrate that "Goal Getter" is effective in enhancing intrinsic motivation, particularly for students with high activity loads in pesantren, and provides practical contributions to the development of learning motivation interventions. ABSTRAK Rendahnya motivasi belajar sering menjadi tantangan bagi siswa, terutama mereka yang memiliki jadwal padat di sekolah dan pesantren. Penelitian ini bertujuan menguji efektivitas pelatihan goal setting "Goal Getter" dalam meningkatkan motivasi belajar siswa pesantren. Menggunakan desain pra-eksperimental one group pre-test post-test, penelitian ini melibatkan tujuh siswa kelas VIII SMPI X. Motivasi belajar diukur dengan Skala Motivasi Belajar yang mencakup indikator dorongan, komitmen, inisiatif, dan optimisme. Uji Wilcoxon Signed-Rank menunjukkan peningkatan signifikan motivasi belajar setelah pelatihan (Z = .043, p < .05). Temuan kualitatif dari observasi dan lembar kerja mengungkapkan peningkatan antusiasme, kepercayaan diri, dan partisipasi aktif siswa. Pelatihan terdiri dari dua sesi yang mencakup materi motivasi, visualisasi pohon impian, penyusunan tujuan dengan metode SMART, dan diskusi reflektif. Pendekatan interaktif membantu siswa menetapkan tujuan yang lebih terarah dan bermakna. Hasil penelitian ini menunjukkan bahwa "Goal Getter" efektif meningkatkan motivasi intrinsik, terutama bagi siswa dengan aktivitas tinggi di pesantren, dan memberikan kontribusi praktis dalam pengembangan intervensi motivasi belajar.